STUDY OF POTENCY AREA FOR SOLAR ENERGY GENERATOR (CASE STUDY IN REGION OF EAST JAVA) - TAMAMADIN , MAMAD
As tropical state, Indonesia has the potency of solar energy with mean of daily solar radiation equal to 4.8 l kWh/m2 which can conducively build solar energy generator. But in development of solar energy generator is still considering region that is not distributed by on-grid electric power caused difficult build it and estimating solar power that is incident on surface of the region. SMARTS (Simple Model of the Atmospheric Radiative Transfer of Sunshine) helps to estimate solar power in every wavelength. NCEP Reanalysis data and PLN distributing map is used to determine where area that has potency. SMARTS model estimates irradiance per wavelength by calculating many factors of meteorology which is taken from observers. The results will be converted to electric power using solar cell efficiency. Some parts of East Java area have potency to build generator after considering the data. The results show that average electric power for a solar cell panel is 86.01 Watt for Pasuruan, 82.98 Watt for Kedawung, 82.32 for Jatiroto, 82.18 Watt for Banyuwangi, 83.10 Watt for Tretes, and 82.36 Watt for Wingin Anom. If electric power at East Java is compared to electric power at Serre Italia which has 55 Watt for one panel of solar cell , so this is proving tropical area more potential than subtropical area.